2016
DOI: 10.1016/j.psyneuen.2016.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Altered metabolic parameters in association with antipsychotic medication use in diabetes: A population based case-control study

Abstract: Altered metabolic parameters in association with antipsychotic medication use in diabetes Wake, D. J.; Broughton, P.; Perera, S. M.; MacIntyre, D. J.; Leese, G. P. Published in: Psychoneuroendocrinology DOI:10.1016/j.psyneuen.2016.01.022 Publication date: 2016 Document Version Peer reviewed version Link to publication in Discovery Research PortalCitation for published version (APA): Wake, D. J., Broughton, P., Perera, S. M., MacIntyre, D. J., & Leese, G. P. (2016). Altered metabolic parameters in association w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Our study is the first to comparatively evaluate markers of cardiovascular risk factors in people with SMI using longitudinal data. Two previous studies, one a case–control study (matching patients with schizophrenia with controls on factors including BMI) and one a cross‐sectional study, observed significantly lower HbA 1c levels in SMI groups compared with non‐SMI groups (Dixon et al, ; Wake et al, ). We observed no significant initial difference in mean HbA 1c between groups, but we included patients without schizophrenia and did not follow the same matching approach.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our study is the first to comparatively evaluate markers of cardiovascular risk factors in people with SMI using longitudinal data. Two previous studies, one a case–control study (matching patients with schizophrenia with controls on factors including BMI) and one a cross‐sectional study, observed significantly lower HbA 1c levels in SMI groups compared with non‐SMI groups (Dixon et al, ; Wake et al, ). We observed no significant initial difference in mean HbA 1c between groups, but we included patients without schizophrenia and did not follow the same matching approach.…”
Section: Discussionmentioning
confidence: 97%
“…Controlling HbA 1c and optimising lipid and blood pressure management reduce the risks of microvascular and macrovascular complications, which remain the main cause of morbidity and mortality in patients with T2DM (Collaborators, 2008;Khaw, Wareham, & Luben, 2001;Ray et al, 2009;UK Prospective Diabetes Study Group, 1998). However, the evidence for appropriate management of cardiovascular risk factors in patients with diabetes and SMI is inconclusive, particularly in the UK (Dixon et al, 2004;Wake, Broughton, Perera, MacIntyre, & Leese, 2016). A small study in the United States showed that patients with SMI had lower levels of HbA 1c compared to patients without SMI (Dixon et al, 2004), and a recent larger study suggested that people with T2DM taking antipsychotic medication have lower cholesterol, HbA 1c and blood pressure levels compared with matched controls not taking antipsychotic medication (Wake et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just four studies reported on antipsychotic prescribing in relation to diabetes outcomes. The two studies that investigated the association between antipsychotic prescribing and clinical complications of diabetes used population-based national registers [24, 32]. A cohort study of people with schizophrenia found that, compared to no antipsychotic prescribing, regular antipsychotic prescribing was associated with a 20% and 27% reduced risk of cardiovascular morbidity, and all-cause mortality, respectively [24] (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Details of the antidepressant and antipsychotic drugs included with each study are given in Supplemental Table 2. Eleven studies were cohort [16][17][18][19][20][21][22][23][24][25][26], one was a self-controlled before and after study [27], two were case-control [28,29], and four were cross-sectional studies [30][31][32][33]. Two studies included overlapping study populations [21,27], but adopted different study designs to address a similar question and so both were included in the narrative synthesis.…”
Section: Study Characteristicsmentioning
confidence: 99%